ANALISIS BEBAN EMISI KENDARAAN DI GERBANG MASUK JALAN-JALAN ARTERI KE KOTA JAMBI - Rizki Andre Handika; Zuli Rodhiyah; Wathri Fitrada; Annisa Purnama Sari (Dampak, 2019)
The City of Jambi has three entering gateways for people from other places to get in using arterial roads. Two roads link Jambi City with South Sumatera, West Sumatera and also Riau Provinces, and one another connects to West Tanjung Jabung and East Tanjung Jabung Regencies. Many vehicles, starting from individual cars and motor cyclesuntil HDV with more dimensions such as trailer truck, have increased air pollution and would generate effect to human health. The research aimed to estimate the load emission from mobile sources on those gateways using Mobilev 3.0 software, and converted the results using Microsoft Excel for advance analysis. Data input came from the number of vehicles from General Sudirman Street, West Ring Road, Surya Dharma Street, South Ring Road, East Ring Road, and Yos Sudarso Street which was enumerated by direct observation using traffic counting method. The results showed that the highest emission (ton/year) to CO and HC was from General Sudirman Street and for CO2, NOx, PM10, and soot was from South Ring Road. The total average daily traffic (ADT) was 435,684.30 units of vehicles per 24 hours, which the biggest was in General Sudirman Street with 114,451.30 units of vehicles per 24 hours. Through this research, both the emission load and also the traffic load situation in each road could be described and became the important information on road transportation management related to ambient air pollution and greenhouse gases controlling.